An empirical evaluation of camera trap study design: How many, how long and when?. Issue 6 (2nd April 2020) - Kays, Roland; Arbogast, Brian S.; Baker‐Whatton, Megan; Beirne, Chris; Boone, Hailey M.; Bowler, Mark; Burneo, Santiago F.; Cove, Michael V.; Ding, Ping; Espinosa, Santiago; Gonçalves, André Luis Sousa; Hansen, Christopher P.; et al.
Abstract: Camera traps deployed in grids or stratified random designs are a well‐established survey tool for wildlife but there has been little evaluation of study design parameters. We used an empirical subsampling approach involving 2, 225 camera deployments run at 41 study areas around the world to evaluate three aspects of camera trap study design (number of sites, duration and season of sampling) and their influence on the estimation of three ecological metrics (species richness, occupancy and detection rate) for mammals. We found that 25–35 camera sites were needed for precise estimates of species richness, depending on scale of the study. The precision of species‐level estimates of occupancy (ψ) was highly sensitive to occupancy level, with <20 camera sites needed for precise estimates of common (ψ > 0.75) species, but more than 150 camera sites likely needed for rare (ψ < 0.25) species. Species detection rates were more difficult to estimate precisely at the grid level due to spatial heterogeneity, presumably driven by unaccounted habitat variability factors within the study area. Running a camera at a site for 2 weeks was most efficient for detecting new species, but 3–4 weeks were needed for precise estimates of local detection rate, with no gains in precision observed after 1 month. Metrics for all mammal communities were sensitive to seasonality, with 37%–50% of the species at the sites we examined fluctuating significantly in their occupancy or detection rates over the year. This effect was more pronounced in temperate sites, where seasonally sensitive species varied in relative abundance by an average factor of 4–5, and some species were completely absent in one season due to hibernation or migration. We recommend the following guidelines to efficiently obtain precise estimates of species richness, occupancy and detection rates with camera trap arrays: run each camera for 3–5 weeks across 40–60 sites per array. We recommend comparisons of detection rates be model based and include local covariates to help account for small‐scale variation. Furthermore, comparisons across study areas or times must account for seasonality, which could have strong impacts on mammal communities in both tropical and temperate sites. RESUMEN: Las trampas cámara desplegadas en cuadrículas o diseños aleatorios estratificados son una herramienta bien establecida para inventarios de vida silvestre, pero ha habido poca evaluación de los parámetros de diseño del estudio. Utilizamos un enfoque empírico de submuestreo que involucra 2, 225 implementaciones de cámaras en 41 áreas de estudio en todo el mundo para evaluar tres aspectos del diseño del estudio de trampa cámara (número de sitios, duración y temporada de muestreo) y su influencia en la estimación de tres métricas ecológicas (riqueza de especies, ocupación y tasa de detección) para mamíferos. Encontramos que se necesitaban 25–35 sitios de cámara para estimar con precisión la riqueza de especies, dependiendo de la escala del estudio. La precisión de las estimaciones de ocupación a nivel de especie (ψ) fue muy sensible al nivel de ocupación, con menos de 20 sitios de trampas cámara necesarios para estimaciones precisas de especies comunes (ψ > 0.75), pero es probable que se necesiten más de 150 sitios de trampas cámara para especies raras (ψ < 0.25) especies. Las tasas de detección de especies fueron más difíciles de estimar con precisión a nivel de cuadrícula debido a la heterogeneidad espacial, presumiblemente impulsada por factores de variabilidad del hábitat no contabilizados dentro del área de estudio. Hacer funcionar una cámara en un sitio durante dos semanas fue más eficiente para detectar nuevas especies, pero se necesitaron de tres a cuatro semanas para estimar con precisión la tasa de detección local, sin ganancias de precisión observadas después de un mes. Las métricas para todas las comunidades de mamíferos fueron sensibles a la estacionalidad, el 37%–50% de las especies en los sitios que examinamos fluctuaron significativamente en sus tasas de ocupación o detección durante el año. Este efecto fue más pronunciado en sitios templados, donde las especies estacionalmente sensibles variaron en abundancia relativa en un factor promedio de 4–5, y algunas especies estuvieron completamente ausentes en una temporada debido a hibernación o migración. Recomendamos las siguientes pautas para obtener de manera eficiente estimaciones precisas de la riqueza de especies, la ocupación y las tasas de detección con matrices de cámaras trampa: desplegar cada cámara durante 3–5 semanas en 40–60 sitios por arreglo. Recomendamos que las comparaciones de las tasas de detección se basen en modelos e incluyan covariables locales para ayudar a explicar la variación a pequeña escala. Además, las comparaciones entre áreas o tiempos de estudio deben tener en cuenta la estacionalidad, que podría tener un fuerte impacto en las comunidades de mamíferos tanto en sitios tropicales como templados. 摘要: 红外相机是一种成熟的野生动物调查工具, 通常以网格化或分层随机的方案布设, 但目前很少有研究评估红外相机技术的实验设计参数。 我们对全球41个研究区域内的2225台相机数据使用二次抽样方法评估了红外相机实验设计的三个参数（相机位点数、监测时长和季节, 及其对估计兽类群落物种数、占有率和探测率的影响。 取决于研究尺度, 我们发现需要25–35个相机位点才能精确估计物种数。物种水平占有率（ ψ）估计的精确度对占有率大小非常敏感: 对于常见种（ ψ > 0.75), 不到20个相机位点便可以精确估计物种的占有率, 但是对于稀有种（ ψ < 0.25）, 则需要150个甚至更多的相机位点。由于空间异质性, 基于网格化布设的红外相机更难以精确地估计物种的探测率, 这大概是由于所在研究区域内未解释的生境差异因素所导致的。在同一个位点持续监测2周可以最有效地探测到新物种, 但是精确估计本地探测率则需要3–4周, 而持续置放1个月后不会继续提高估计的精确度。所有兽类群落的生态指标（物种数、占有率和探测率）都对季节性敏感。在本研究的相机位点内, 37%–50%的物种在一年中占有率或探测率具有非常显著的波动。这种影响在温带地区更为明显: 温带地区对季节性敏感的物种的相对丰度变化幅度为平均的4–5倍, 并且一些物种因冬眠或迁徙会在一个季节内完全不出现。 为了有效地获得红外相机阵列中物种数、占有率和探测率的精确估计, 我们建议以下调查准则: 每批红外相机至少需布设40–60个相机位点, 且每台相机持续监测3–5周。我们建议探测率的比较研究需要基于模型, 并包括局部协变量以帮助解释小尺度的差异。此外, 不同研究区域或时间之间的比较必须考虑季节的因素, 因为季节性可能对热带和温带地区的兽类群落产生强烈的影响。